2018
DOI: 10.1038/s41563-018-0058-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced spin pumping into superconductors provides evidence for superconducting pure spin currents

Abstract: Unlike conventional spin-singlet Cooper pairs, spin-triplet pairs can carry spin. Triplet supercurrents were discovered in Josephson junctions with metallic ferromagnet spacers, where spin transport can occur only within the ferromagnet and in conjunction with a charge current. Ferromagnetic resonance injects a pure spin current from a precessing ferromagnet into adjacent non-magnetic materials. For spin-singlet pairing, the ferromagnetic resonance spin pumping efficiency decreases below the critical temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
184
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(204 citation statements)
references
References 33 publications
16
184
3
Order By: Relevance
“…Interestingly, almost a decade ago, theoretical studies [15,16] suggested a time-varying magnetization M(t) of the FM as a reciprocal equivalent to M(x) for the generation of spin-polarized triplet supercurrents in a diffusive metallic FJJ [15] and also in a FM/NM/SC structure (NM: normal metal) [9]. However, subsequent ferromagnetic resonance (FMR) studies on Nb/Ni80Fe20 bilayers [17,18] and Nb/Ni80Fe20/Nb trilayers [19] have shown that spin angular momentum transfer in such structures is predominantly mediated by quasiparticles (QPs) for the superconducting state and thus largely suppressed at a lower temperature T by the development of singlet superconductivity and the freeze-out of available QP states [17,20,21]. This is likely because the magnitude of M(t) inhomogeneity or noncollinearity, parameterized by the magnetization precession angle θM, is too small (a few degrees at 10-20 GHz) [17][18][19] to yield the measurable effect of M(t)-induced triplet supercurrents [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, almost a decade ago, theoretical studies [15,16] suggested a time-varying magnetization M(t) of the FM as a reciprocal equivalent to M(x) for the generation of spin-polarized triplet supercurrents in a diffusive metallic FJJ [15] and also in a FM/NM/SC structure (NM: normal metal) [9]. However, subsequent ferromagnetic resonance (FMR) studies on Nb/Ni80Fe20 bilayers [17,18] and Nb/Ni80Fe20/Nb trilayers [19] have shown that spin angular momentum transfer in such structures is predominantly mediated by quasiparticles (QPs) for the superconducting state and thus largely suppressed at a lower temperature T by the development of singlet superconductivity and the freeze-out of available QP states [17,20,21]. This is likely because the magnitude of M(t) inhomogeneity or noncollinearity, parameterized by the magnetization precession angle θM, is too small (a few degrees at 10-20 GHz) [17][18][19] to yield the measurable effect of M(t)-induced triplet supercurrents [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The above fitting is consistent with the H=0 limit. A common requirement to realize SOC-driven emergent phenomena, from topological insulators, Majorana fermions, and LRT is typically SOC that is already inherently strong in the normal state, for example, implemented with heavy elements and in narrow-band semiconductors [8,9,16,34]. In contrast, the platform we have studied reveals a peculiar superconducting behavior even when a rather weak SOC in the normal state leads to a negligible magnetic anisotropy.…”
mentioning
confidence: 99%
“…The development of spintronics had already benefited from the use of superconducting materials, resulting in longer spin lifetimes and energy-efficient components [4,5]. Now, triplet supercurrents formed by spin-polarized Cooper pairs add the possibility of transporting a net spin component at zero resistance and thus pave the way for spintronic devices that are less liable to overheat [6][7][8][9][10][11][12][13][14][15][16]. The key challenge in the field is the nonequilibrium and on-demand generation of equal-spin Cooper pairs in a viable fashion [17][18][19][20][21], desirably avoiding the complicated manipulation of magnetic components.…”
mentioning
confidence: 99%